A clinical analysis of 58 chinese cases of pigmented fungiform papillae of the tongue. (16th August 2012) - Tan, C.; Liu, Y.; Min, Z.‐S.; Zhu, W.‐Y.
Abstract Background Pigmented fungiform papillae of the tongue (PFPT) is a disorder in which the fungiform papillae of the tongue have abnormal coloration. However, Chinese‐specific clinical data for PFPT are lacking. Objective To determine the prevalence and characteristics of PFPT among the Chinese population. Methods A survey was carried out using a clinical examination and a questionnaire on 14, 346 first‐time outpatients in our dermatology department, and 58 cases of PFPT were subsequently diagnosed. Results The prevalence of PFPT was 0.4% among dermatological outpatients. All patients had pin‐sized, brownish fungiform papillae on the tip, lateral or dorsal parts of the tongue. Of the three subtypes, type I was the most common (87.93%). PFPT generally coexisted with Hori's nevus (48.28%), melasma (20.69%), hysteromyoma (24.14%) and breast cystic hyperplasia (20.69%). Conclusion Our study confirms that PFPT is a relatively common disorder among Chinese outpatients, and it was presumed to be closely coupled with Hori's nevus, melasma and other disorders.